Mengembangkan Kelompok Pemusik Melalui Relief Tentang Musik di Candi Borobudur - Widya Nayati (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
Learning can be done by anyone and anywhere. Cultural heritage provides an alternative interestinglearning resource. It is just that not many people understand the benefts that can be obtained fromcultural heritage. Tis Community Service by FIB UGM in 2018 made an eﬀort so that peoplewould be more familiar with learning resources from cultural heritage objects. Te objects used inthis study are reliefs which depict a music group from the Borobudur Temple. Tis choice is basedon Gardner's theory which states that every human being has a diﬀerent intelligence. Among thenine intelligences presented by Gardner, musical intelligence is one of them. By applying Gardner'stheory, especially musical intelligence, the introduction of objects of relief about people playing musicfrom Borobudur reliefs to people who like music is expected to be able to facilitate them to capturethe message conveyed.Reliefs about people playing music from Borobudur Temple is introduced to a group of musicians,namely the Pesantian Wisnu Sakti Tambakan group located in Tambakan Village, JogonalanDistrict, Klaten Regency. Te way to do this is to look at and imitate body movements such as thosedepicted on the reliefs of musicians playing musical instruments at Borobudur Temple. Te resultof the observations show that the participants feel the beauty of the movements and feel the sound ofthe music produced with the position of the hands and the appropriate instruments so as to producebeautiful and unique sounds. From the process of the activities carried out, this group was able toproduce several pieces of music. Te music produced also make the participants feel happy and planto use the results of this learning for various activities.